Estudio de Impacto Ambiental (ex – post) del relleno sanitario de la ciudad de Cariamanga perteneciente al cantón Calvas - Quinteros Reyes, Galo Adrian (2024)
An Environmental Impact Study was conducted in this research project in order to analyze and prevent the adverse effects of the operation of the sanitary landfill. This was done in the Cango Alto area of Cariamanga parish. To conduct this study, a diagnosis of the current situation in the influence area was made. This was followed by the identification and evaluation of possible environmental and socioeconomic impacts. There was then a proposal for an environmental management plan containing all the necessary measures to prevent, mitigate, and correct potential impacts on natural resources. During the noise monitoring, values exceeding the permissible limits established by the TULSMA (UNIFIED TEXT OF SECONDARY LEGISLATION ON ENVIRONMENT) and the WHO (WORLD HEALTH ORGANIZATION), were obtained. These values registered 83.3 and 75 dB during daytime hours both in the waste unloading area and at the landfill entrance. It had a 70 dB limit. During water characterization, the iron, chromium and nitrite parameters exceeded the permissible limits established in TULSMA and the WHO. In relation to the soil, a low non-saline (NS) electrical conductivity was evident, which could indicate a lack of nutrients or moisture in the soil. Subsequently, the environmental impacts in the area generated by the activities to be carried out during the operation and closure phase of the landfill were evaluated and identified. These impacts identified 19 impacts, of which 15 are environmental and 4 are socioeconomic, with the operation phase producing the most detrimental impacts. Finally, with all the information obtained, an Environmental Management Plan was prepared containing 8 sub-plans with the necessary measures to prevent, mitigate and correct potential impacts on natural resources.